Human Epididymis Protein 4: A Novel Biomarker for Lupus Nephritis and Chronic Kidney Disease in Systemic Lupus Erythematosus. Issue 6 (13th April 2016) - Yang, Zaixing; Zhang, Zhiyu; Qin, Baodong; Wu, Ping; Zhong, Renqian; Zhou, Lin; Liang, Yan
Abstract : Background: Human epididymis protein 4 (HE4) is an available tumor biomarker for detecting ovarian cancer. However, it is unknown if serum HE4 could be a novel biomarker for diagnosis of lupus nephritis (LN) and chronic kidney disease (CKD) in patients with systemic lupus erythematosus (SLE). Methods: This study enrolled 209 SLE patients, 75 patients with renal dysfunction without SLE and 32 healthy subjects. HE4 concentrations were analyzed by ELISA (enzyme‐linked immunosorbent assay; Fujirebio Diagnostics, Sweden). The receiver operating characteristic (ROC) curves were constructed to assess diagnostic accuracy of HE4 for LN or CKD in SLE. Results: Serum HE4 level was significantly higher in SLE patients than that in healthy controls ( P < 0.001), especially for those with LN or CKD. It was also higher in patients with renal dysfunction without SLE than healthy controls ( P < 0.001), while there was no significant difference between these patients and those with SLE with CKD ( P = 0.73). Multivariate analysis showed significant association between increased HE4 and LN or CKD after controlling for confounders. ROC curves showed the cutoff values were 150.1 pM (sensitivity, 76.8%; specificity, 91.1%) for the diagnosis of LN in SLE and 233.9 pM (sensitivity, 92.9%; specificity, 93.5%) for CKD in SLE. Conclusions: Increased serum HE4 level is closely associated with the development of LN or CKD in SLE patients. Furthermore, it can be used as a novel and useful biomarker for diagnosis of LN or CKD.